THE READINESS OF THE BRIDGE PROSPECTIVE IN BUILDING A HOUSEHOLD IN KEPANJEN KIDUL DISTRICT - Ditya Nurul Asikin; Sri Mugianti; Muhammad Miftachul Ulum; Tri Anjaswarni (Universitas Islam Balitar, 2023)
Marriage is a bond of sacred promise between individual men and women which aims to perfect a lawful relationship. The bride and groom must be well prepared before getting married. The purpose of this study was to determine the readiness of the bride and groom in building a household. The design used is qualitative, data collection by in-depth interviews, using purposive sampling technique, with research subjects 4 prospective brides. The focus of the study includes the readiness of the bride and groom, sources of experience, and efforts to maintain the household. The results of the study found the theme of facilities provided by the government with no obligations and information about official premarital education. The theme of the readiness of the bride and groom includes physical readiness by conducting a health check, social readiness by knowing the background of the couple for a long time, and getting the age maturity to get married. The theme of sources of experience from parents and friends about plans to live a married life, from the internet and school education about sex education. Possible problem themes include economic problems, poor communication with partners, rights and obligations, differences of opinion, and domestic violence. The theme is efforts to strengthen household resilience by establishing good communication with partners. Pre-marital preparation regulations need to be socialized in the community, especially among teenagers